2011
DOI: 10.1637/9775-050911-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza and Newcastle Disease in Three Risk Areas for H5N1 Highly Pathogenic Avian Influenza in Mali, 2007–2008

Abstract: Our survey aimed to investigate avian influenza (AI) and Newcastle disease (ND) prevalence and risk factors in three areas of Mali at risk for occurrence of H5N1 highly pathogenic avian influenza. Blood samples and cloacal and oropharyngeal swabs were collected from 1470 birds between February 2007 and May 2008 and were tested by commercial enzyme-linked immunosorbent assay to detect antibodies and real-time reverse-transcription (rRT)-PCR to detect virus. Risk factors associated with seropositivity or positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However this may not be the only explanation for monthly variations as seroprevalence remained over 25% in January and March, with broilers representing 64% and 62% of the flocks sampled at that period of time. It has also been suggested that AIV prevalence may vary with contacts between poultry and wild birds and virus survival under environmental conditions, including temperature [31]. At last, between-flock seroprevalence might also be influenced by the seasonality of poultry production and trade in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…However this may not be the only explanation for monthly variations as seroprevalence remained over 25% in January and March, with broilers representing 64% and 62% of the flocks sampled at that period of time. It has also been suggested that AIV prevalence may vary with contacts between poultry and wild birds and virus survival under environmental conditions, including temperature [31]. At last, between-flock seroprevalence might also be influenced by the seasonality of poultry production and trade in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…In Mali, the same cross-sectional prevalence survey was carried out in May 2008 on chickens and ducks. This period corresponds to the end of the dry-hot season, with an average temperature of 32 • C. The whole protocol design is described in [49]. The study population was the backyard poultry population of villages known to raise ducks by the agents of the Regional Directorates of Veterinary Services of Mopti.…”
Section: Data Collectionmentioning
confidence: 99%
“…The study population was the backyard poultry population of villages known to raise ducks by the agents of the Regional Directorates of Veterinary Services of Mopti. Villages and farms were conveniently chosen, based on accessibility criteria and owners' willingness [49].…”
Section: Data Collectionmentioning
confidence: 99%
“…Natural co-infections of NDV and LPAIV have been documented numerous times in wild waterfowl and in domestic poultry (Couacy-Hymann et al, 2012; Dormitorio et al, 2009; Hanson et al, 2005; Molia et al, 2011; Rosenberger et al, 1974; Roussan et al, 2008; Shortridge, 1980). However, little is known on the interactions between these two viruses when simultaneously infecting poultry species including domestic ducks.…”
Section: Introductionmentioning
confidence: 99%